Evolutionary forces at work in partitiviruses - Petrzik, Karel (Virus genes, 2019)
The family Partitiviridae consists of dsRNA viruses with genome separated into two segments and encoding replicase and capsid protein only. We examined the nucleotide diversity expressed as the ratio dN/dS of nonsynonymous and synonymous substitutions, which has been calculated for 12 representative viruses of all five genera of partitiviruses. We can state that strong purifying selection works on both the RdRp and CP genes and propose that putative positive selection occurs also on the RdRp genes in two viruses. Among the 95 evaluated viruses, wherein both segments had been sequenced, 8 viruses in betapartitiviruses and 9 in alphapartitiviruses were identified as reassortment candidates because they differ extremely in their CP identity even as they are related in terms of RdRp. Furthermore, there are indications that reassortants are present among isolates of different viruses.
Keywords: Evolution, Molecular; virové plášťové proteiny; molekulární evoluce; RNA, Double-Stranded; genetická variace; dvouvláknová RNA; RNA virová; mutace; RNA-dependentní RNA-polymerasa; Genetic Variation; RNA-viry; RNA, Viral; Capsid Proteins; Mutation; RNA Viruses; RNA-Dependent RNA Polymerase